2021
DOI: 10.1039/d0ma00984a
|View full text |Cite
|
Sign up to set email alerts
|

PET waste as organic linker source for the sustainable preparation of MOF-derived methane dry reforming catalysts

Abstract: A catalyst made of Ni0 nanoparticles highly dispersed on a lamellar alumina support was prepared by an environmentally-friendly route. The latter involved the synthesis of an aluminum-containing metal-organic framework (MOF)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…Figure S1 shows the nitrogen isotherm adsorption and desorption results of the catalysts. The type IV hysteresis loop is identified in all catalysts, which indicates that the catalysts have mesoporous structures [16]. The mesoporous structure of Ni-based catalysts is known to provide accessible Ni active centers and to stabilize Ni particles by confinement effect [18].…”
Section: Catalyst Characterizationmentioning
confidence: 86%
See 1 more Smart Citation
“…Figure S1 shows the nitrogen isotherm adsorption and desorption results of the catalysts. The type IV hysteresis loop is identified in all catalysts, which indicates that the catalysts have mesoporous structures [16]. The mesoporous structure of Ni-based catalysts is known to provide accessible Ni active centers and to stabilize Ni particles by confinement effect [18].…”
Section: Catalyst Characterizationmentioning
confidence: 86%
“…The CO 2 reforming of CH 4 (CDR: CH 4 + CO 2 → 2CO + 2H 2 ) has the advantage of using CH 4 and CO 2 as reactants to produce syngas, which is an elemental raw material with high added value [15]. In addition, the syngas produced by the dry reforming reaction (H 2 :CO = 1:1) shows a favorable H 2 :CO ratio for oxo compound synthesis compared to the syngas produced through the steam reforming reaction (H 2 :CO = 3:1) [16]. However, as the dry reforming reaction proceeds at high temperatures above 700 • C, favorable conditions are formed for sintering of active metals and supports to occur, and catalyst deactivation may occur due to carbon deposition by methane decomposition [17].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several reports have already demonstrated that several MOFs can be synthesized using PET as a starting material (Figure 4A). [78][79][80][81][82] The synthetic details of making MOFs out of PET derived terephthalate have already been well reviewed by El-Sayed and Yuan, 78 and we will therefore focus on reports with specific applications towards CO 2 capture and utilization.…”
Section: Plastic-derived Metal Organic Framework (Mofs)mentioning
confidence: 99%
“…4A). [78][79][80][81][82] The synthesis details of making MOFs out of PET derived terephthalate have already been well reviewed by El-Sayed and Yuan, 78 and we will therefore focus on reports with specific applications towards CO 2 capture and utilization.…”
Section: Plastic-derived Metal-organic Framework (Mofs)mentioning
confidence: 99%
“…6a-c). 17 The MOF ([M 2 (BDC) 2 (DABCO)]) produced utilizing waste PET material through one-pot synthesis has an isostructural morphology with different central metal atoms such as Fe, Co, Ni, Cu, and Zn. The above MOF productions are done at 120 1C for 48 h with a yield of about 90 to 95%.…”
Section: Metal-organic Framework (Mofs)mentioning
confidence: 99%